1997
DOI: 10.1002/(sici)1096-9136(199706)14:6<442::aid-did386>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence for a high incidence of nocturnal hypoglycaemia in IDDM: no effect of dose for dose transfer between human and porcine insulins

Abstract: We tested the hypothesis that transfer from porcine to human insulin causes a fall in nocturnal blood glucose and an increase in the frequency of hypoglycaemic episodes. Twenty IDDM patients (age 19–55, duration 3–36 years) used Velosulin and Insulatard twice daily for 12 weeks, double‐blinded to species (human (H) or porcine (P)) in a randomized crossover study. Species was changed after 4 weeks’ run‐in and 4 weeks later, with insulin doses unchanged on transfer. Ten patients underwent each sequence (H/P/H or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Two of the studies[11–12] described in Table 1 have only appeared in abstract form to date. Two reports[12–13] in Table 1 and one report[14] in Table 2 also appear in Tables 3 and 4, respectively, as the data they contain pertains to both the population and laboratory settings. The reports by MacLeod[15–16], in Tables 1 and 3, respectively, studied the same subjects in both population and laboratory settings.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two of the studies[11–12] described in Table 1 have only appeared in abstract form to date. Two reports[12–13] in Table 1 and one report[14] in Table 2 also appear in Tables 3 and 4, respectively, as the data they contain pertains to both the population and laboratory settings. The reports by MacLeod[15–16], in Tables 1 and 3, respectively, studied the same subjects in both population and laboratory settings.…”
Section: Resultsmentioning
confidence: 99%
“…All but one[61] provided data on hypoglycaemic events, this study simply reporting no events during the investigation. Four studies found no differences in the frequency of hypoglycaemia[2–64]. Two studies reported a statistically insignificantly increased frequency of hypoglycaemia in subjects on ‘human’ insulin as compared to those on insulin of animal origin[65–66].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that glucose sensing neurones alter their hypoglycaemia sensitivity in response to recent previous glucose experience[10]. The neurohumoral responses to hypoglycaemia during sleep are much less vigorous than in the awake state[11], so nocturnal hypoglycaemia is often unsuspected[12,13]. A single episode of nocturnal hypoglycaemia can diminish the reaction to hypoglycaemia the next day, increasing the risk of another severe episode[6].…”
Section: What Is the Mechanism Of Hypoglycaemia Unawareness?mentioning
confidence: 99%
“…Strict hypoglycaemia avoidance is not easy as it involves the patient in frequent glucose monitoring to discover times of asymptomatic hypoglycaemia. Nocturnal hypoglycaemia should always be thought of, as hypoglycaemia during the night is often asymptomatic and may reduce the patient's ability to recognize hypoglycaemia in time the next day[6,11–13].…”
Section: Can Mrs Ck Regain Her Awareness Of Hypoglycaemia Without Lmentioning
confidence: 99%